Adolescent Male Reproductive Health Knowledge and Practices in Bangladesh - Ahmed, Faez; Kabir, Abdul Kalam Lutful; Islam, Md Shafiqul; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2009)
Opinions on reproductive health education at the onset of puberty at present were studied by using a structured questionnaire consisting of 13 questions with a view to know their conception about it. A total of 800 male students were randomly selected of which 400 were from two public and the rest 400 from private universities situated in Dhaka, Bangladesh. At least half of the university students (384, 48%) did not understand much about puberty and remained confused. A large number of adolescents felt shy (208, 26%), scared (56, 7%), least bothered (112, 14%) and were not at all aware (40, 5%) of their onset of puberty. The respondents reported to have discussion their pubertal changes mainly with their male peers (672, 84%) and a very little access to parents (16, 2%) and elder brothers (16, 2%). A few respondents talked with their teachers (40, 5%). Their shared feelings were not informative and rather incorrect for maintaining good reproductive health at a growing time. On the contrary, they were rather warned by the persons not to disclose it to others. Most of the respondents (672, 84%) felt sex education is essential for better reproductive health management, a few of them (88, 11%) opposed this idea and some of them remained silent (40, 5%). Half of the respondents (760, 50%) preferred reproductive health education should be included in secondary and higher secondary levels (375, 25%), in the university level (166, 11%) and very few wanted it to be included in primary level (93, 6%). A few number of respondents (92, 6%) preferred non-formal reproductive health education. Some of the respondents (785, 23%) wanted to learn through curriculum and discussion with partners on sexual matter, reproductive organs and their functions (765, 16%), on STIs and AIDS (665, 17%) for safe sexual life. They (580, 11%) want to know the process of pregnancy and lactation, menstruation (356, 7%) and protection from unwanted sex (320, 6%) and other related issues (130, 2%). Most of the respondents (600, 75%) have no clear idea on the impact of addiction on sexual activity. However, a few number of respondents (128, 16%) believed that any drug addiction might cause decreased sexual activity while the other respondents (72, 9%) kept silent. Key words: Adolescent, Male, Reproductive Health, Sex education, Curriculum, Drug addiction, Secondary level. doi: 10.3329/dujps.v7i2.2171 Dhaka Univ. J. Pharm. Sci. 7(2): 149-154, 2008 (December)